2000
DOI: 10.1095/biolreprod63.2.417
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-τ Modulates Phorbol Ester-Induced Production of Prostaglandin and Expression of Cyclooxygenase-2 and Phospholipase-A2 from Bovine Endometrial Cells1

Abstract: Antiluteolytic actions of bovine interferon-tau (bIFN-tau) require suppression of prostaglandin F(2 alpha) (PGF(2 alpha)) production. Our objective was to test whether bIFN-tau could block PGF(2 alpha) production and synthesis of phospholipase A(2) (PLA(2)) and cyclooxygenase-2 (COX-2) enzymes induced by a protein kinase C (PKC) stimulator (phorbol 12,13 dibutyrate; PDBu). Bovine endometrial epithelial (BEND) cells were treated with PDBu in the presence or absence of bIFN-tau. Medium samples were analyzed for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
42
0
4

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 29 publications
4
42
0
4
Order By: Relevance
“…Although embryonic cells, particularly, ICM cells, which are pluripotent, have been well applied to NT for producing cloned offspring in mice, trophoblast cells have not been given much attention. In ruminants, trophoblasts cells at the implantation stage strongly expressed IFNτ, a type I IFN that is considered to be an important signal for antiluteolysis in early pregnancy [30]. Here, we proved the hypothesis that trophoblasts cells expressing IFNτ would be reprogrammed in enucleated oocytes and develop into cloned blastocysts.…”
Section: Discussionsupporting
confidence: 60%
“…Although embryonic cells, particularly, ICM cells, which are pluripotent, have been well applied to NT for producing cloned offspring in mice, trophoblast cells have not been given much attention. In ruminants, trophoblasts cells at the implantation stage strongly expressed IFNτ, a type I IFN that is considered to be an important signal for antiluteolysis in early pregnancy [30]. Here, we proved the hypothesis that trophoblasts cells expressing IFNτ would be reprogrammed in enucleated oocytes and develop into cloned blastocysts.…”
Section: Discussionsupporting
confidence: 60%
“…These differences could be explained in part because, usually, epithelial and stromal cells are cultured separately in vitro, whereas they are free to interact in vivo where the LE is also exposed to higher concentrations of mediators from the conceptus, compared with the stroma. Discrepancies were also reported among in vitro studies conducted by different teams [29][30][31], and distinct responses to IFNmight depend upon the concentration or isoform used [32]. Overall, this reminds us that care must be taken in evaluating observations made in vitro, and that performing in vivo protocols in parallel often offers physiological clarification.…”
Section: Discussionmentioning
confidence: 99%
“…At low doses, IFN-inhibits the expression of cyclooxygenase (COX)-2 and the synthesis of PGs in endometrial epithelial and stromal cells, whereas at high doses it is stimulatory [29][30][31][32]. Thus, IFN-would either suppress the expression of COX-2 and the production of luteolytic PGF 2␣ or induce COX-2 and the synthesis of luteoprotective/luteotropic PGE 2 [33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…It remains unclear whether the activation of these viral-response genes has any role in preparing the uterus for pregnancy. However, at least three genes, specifically those encoding estrogen receptor-a (ESR1; Spencer et al 1995b, the OTR; Spencer et al 1995a, and cyclooxygenase-2 (PTGS2; Xiao et al 1998, Binelli et al 2000, Pru et al 2001 have been implicated in the antiluteolytic action of IFNT and reported to be down-regulated following IFNT exposure. Confusingly, others have been unable to confirm this result for PTGS2, which has variously been reported to be up-regulated (Asselin et al 1997a, 1997b, Emond et al 2004 or unaffected by IFNT (Kim et al 2003b).…”
Section: Introductionmentioning
confidence: 99%